2017
DOI: 10.31018/jans.v9i2.1341
|View full text |Cite
|
Sign up to set email alerts
|

Influence of rice varieties and fertility levels on performance of rice and soil nutrient status under aerobic conditions

Abstract: Scarcity of water resources in India is limiting the production of flooded rice crop. A field experiment was conducted in factorial RBD with sixteen treatment combinations including four rice varieties viz. V 1 : PR-115, V 2 : DRRH-3, V 3 : PAC-837 and V 3 : PR-121 and four fertility levels viz. , number of seeds per panicle, 1000-grain weight, spikelet sterility and grain yield, straw yield and harvest index significantly differed in different varieties and were recorded highest in PAC-837 which were however,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
4
4
0
Order By: Relevance
“…Nitrogen uptake by grain and straw was significantly highest when the sorghum crop was sown after the harvest of early maturing variety NLR-34449 and this might be due to more availability of nutrients and less uptake by variety NLR-34449 that benefited the succeeding sorghum crop with the highest nitrogen uptake. These results are in compliance with the finding of Kumar et al [19].…”
Section: Nitrogen Uptakesupporting
confidence: 94%
“…Nitrogen uptake by grain and straw was significantly highest when the sorghum crop was sown after the harvest of early maturing variety NLR-34449 and this might be due to more availability of nutrients and less uptake by variety NLR-34449 that benefited the succeeding sorghum crop with the highest nitrogen uptake. These results are in compliance with the finding of Kumar et al [19].…”
Section: Nitrogen Uptakesupporting
confidence: 94%
“…Whereas much higher number of tillers were recorded through application of 150 kg N ha -1 as reported by Ramesh et al (2009). Similarly, positive response to Nitrogen application has been reported by Shukla et al (2015) at 120 kg N ha -1 with effective tillers (238.50 m -2 ), Kumar et al (2017) at 150 kg/ha (9.25 EBT hill -1 ) under aerobic condition and Dahipahle and Singh (2018) at 180 kg N ha -1 (12.6 EBT hill -1 ) under puddle soils.…”
Section: Plant Heightsupporting
confidence: 51%
“…Similar results were obtained before by Setiawati et al, (2020) who, evaluated two rice cultivars under different organic sources and they found significant differences between the two genotypes in all growth and yield traits. Also, Kumar et al, (2017) evaluated the four rice varieties under four NPK levels and they revealed that the four cultivars differ in their growth and yield performances under all NPK levels according to their genetic. Kharel et al, (2018) evaluated rice genotypes under different nutrient levels in artificially created stress conditions during reproductive stages and they reported that the rice genotypes showed significant differences for days to flowering, days to maturity, and grain yield.…”
Section: Discussionmentioning
confidence: 99%